(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Imidazoline derivatives have been synthesized based on the synthetic petroleum acids (SPA) and diethylentriamine. Complexes were prepared from these compounds and HCl in ratio 1:1, 1:2, 1:3. 20% solution of the complexes were prepared in aqueous isopropyl alcohol. The kinetic effect of steel corrosion in 1% NaCl solution saturated with CO2 were studied ACM Gill AC potentiometer. It was found that, the imidazoline derivatives complexes based on the SPA and DETA with HCl in molar ratio 1:1 of 25 ppm concentration protection from corrosion is 83,5%, 100 ppm Â concentration â€“ 97,1%; the proportion of 1:2 complex of Â 25 ppm â€“ 82,8%, 100 ppm Â concentration â€“ 97,3%, but in the case of the 1:3 complex shows the best result - 94 and 98,8%.